Uptake of milk with and without solid feed during the monogastric phase: Effect on fibrolytic and methanogenic microorganisms in the gastrointestinal tract of calves. (7th August 2015) - Guzman, Cesar E.; Bereza‐Malcolm, Lara T.; De Groef, Bert; Franks, Ashley E.
Abstract: Microbial communities are affected by diet and play a role in the successful transition from milk to a solid diet. The response of microorganisms in the gastrointestinal tract of Holstein bull calves to the uptake of milk with solid feed (control treatment; CT), or milk without solid feed (milk‐only treatment; MT) during the first 3 weeks of life was investigated. Samples were collected from the rumen (fluid and tissue), abomasum (fluid), cecum (fluid and tissue) and feces at 7, 14 and 20 days of age. Calf weight was higher on days 14 and 20 in the MT than the CT. In the rumen at 14 days, the fibrolytic bacteria Fibrobacter succinogenes and Prevotella ruminicola increased in the CT and Ruminococcus flavefaciens increased in the MT. This suggests that R . flavefaciens is not strictly fibrolytic and that it might use milk as a substrate or other microbial species might supply a substrate. Diet affected methanogens, but this may have been due to an indirect effect via an association with Geobacter spp. or other syntrophic partners. The treatments also affected microorganisms in the abomasum, cecum and feces. Our results contribute to an understanding of diet, microbes in the gastrointestinal tract and weaning.